أثر نظم المعلومات المحاسبية الإلكترونية على فعالية المراجعة الداخلية ( جامعة طبرق أنموذجا) (Comprehensive Journal of Science, 2025)
The aim of this study is to identify the impact of electronic accounting information systems on the effectiveness of internal auditing. To achieve the objectives of this study, the inductive approach was adopted to collect the discussions and debates related to this topic. A questionnaire was designed and distributed to the study sample, and it was analyzed using statistical methods appropriate to the nature of the study and its hypotheses. The study was limited to internal auditors and faculty members in the Accounting Department at the University of Tobruk. The study reached several findings, the most important of which are: electronic accounting information systems create a significant practical difference in internal auditing methods; tracking the path of electronic financial operations is considered one of the most essential improvements in the field of auditing; and the use of electronic accounting information systems has reshaped the tasks of the internal auditor within the university, making their responsibilities more closely related to technical activities. Based on the results obtained, the researchers recommend supporting the need to train internal auditors and develop their technical capabilities in line with the environment of electronic accounting information systems, as well as identifying the practical and technical challenges associated with implementing electronic systems in detail, including the difficulty of adapting to complex system environments and the risks of technical failures.
Keywords: systems, information, accounting, electronic, auditing, internal.